2016
DOI: 10.14238/sp14.4.2012.235-40
|View full text |Cite
|
Sign up to set email alerts
|

Kejadian Infeksi Saluran Kemih di Ruang Rawat Inap Anak RSUD Dr. Zainoel Abidin Banda Aceh

Abstract: Kata kunci: infeksi saluran kemih, kuman penyebab, sensitivitas antibiotik

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
(12 reference statements)
0
4
0
3
Order By: Relevance
“…13 Escherichia coli had low level of susceptibility to cephalosporin class, such as Cefadroxil (0%), Cefazolin (30%), Ceftazidime (40%), Ceftriaxone (40%), 14 reported higher susceptibility percentage of Escherichia coli to Ceftriaxone (52.2%). High resistance to Ceftazidime and Ceftriaxone was supported by the study by Haris et al 15 High level susceptibility to Amikacin (50%), Levofloxacin (50%), and Cotrimoxazole (50%) was found on Klebsiellapneumoniae isolates. In comparison, the study by Waadallah et al 10 showed Klebsiellapneumoniae was susceptible to Amikacin (100%) and Cotrimoxazole (80%).…”
Section: Enterococcus Faecalismentioning
confidence: 72%
“…13 Escherichia coli had low level of susceptibility to cephalosporin class, such as Cefadroxil (0%), Cefazolin (30%), Ceftazidime (40%), Ceftriaxone (40%), 14 reported higher susceptibility percentage of Escherichia coli to Ceftriaxone (52.2%). High resistance to Ceftazidime and Ceftriaxone was supported by the study by Haris et al 15 High level susceptibility to Amikacin (50%), Levofloxacin (50%), and Cotrimoxazole (50%) was found on Klebsiellapneumoniae isolates. In comparison, the study by Waadallah et al 10 showed Klebsiellapneumoniae was susceptible to Amikacin (100%) and Cotrimoxazole (80%).…”
Section: Enterococcus Faecalismentioning
confidence: 72%
“…Ashoka et al 10 received Escherichia coli followed by Klebsiella pneumoniae as the commonest bacteria found in childhood UTI. Research conducted in Banda Aceh, Indonesia by Haris et al 12 showed the results of Pseudomonas aeroginosa as the most cause, followed by Escherichia coli and Klebsiela. By the distribution of Klebsiella pneumoniae based on age and gender in this study, it was found to be the most common in the age group > 10 years and the boys.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Knowledge of hospital sensitivity patterns is indispensable for use as a reference in the use of antibiotics. 12 The pattern of bacterial sensitivity to antibiotics is rapidly changing over time, especially in developing countries, so proper selection of antibiotics is essential in UTI therapy. 6,13 The presence of different pattern of bacteria causing UTI in children in each region as well as the increasing number of antibiotic resistance to pathogenic bacteria causing UTI so it needs to be updated data periodically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pada kelompok anak usia muda gejala ISK tidak spesifik sehingga dapat menyebabkan keterlambatan diagnosis dan terapi. [1][2][3][4][5][6][7] Tahun 2011, American Academy of Pediatrics (AAP) melakukan revisi pedoman untuk diagnosis dan manajemen ISK pada anak usia 2-24 bulan. Pedoman ini ditujukan untuk membantu klinisi dalam menangani ISK, menentukan pemeriksaan urinalisis, dan terapi pada anak di poliklinik dan ruang gawat darurat.…”
Section: Ikhsan Trinadi Dkk: Validasi Kriteria Diagnosis Isk Berdasarunclassified